Using dopamine interlayers to construct Fe/Fe3C@FeNC microspheres of high N-content for bifunctional oxygen electrocatalysts of Zn–air batteries. Issue 8 (31st January 2023) - Huang, Naibao; Dong, Wenjing; Feng, Yuan; Liu, Wei; Guo, Likui; Xu, Jingnan; Sun, Xiannian
Abstract : The PDA interlayer serves as a buffer agent to avoid destruction of template. Abstract : High activity bifunctional oxygen electrocatalysts are crucial for the development of high performing Zn–air batteries. Fe–N–C systems decorated with Fe/Fe3 C nanoparticles have been identified as prospective candidates in which almost all the active sites need the presence of N. To anchor more N, an Fe2 O3 microsphere template was covered by a thin layer of polymerized dopamine (PDA) before it was mixed with a high N-content source of g-C3 N4 . The PDA interlayer not only provides a part of C and N but also serves as a buffer agent to hinder fast reactions between Fe2 O3 and g-C3 N4 during pyrolysis to avoid the destruction of the microsphere template. The prepared Fe/Fe3 C@FeNC catalyst showed superior electrochemical performance, achieving a high half-wave potential of 0.825 V for ORR and a low overpotential of 1.450 V at 10 mA cm −2 for OER. The rechargeable Zn–air battery assembled with the as-obtained Fe/Fe3 C@FeNC catalyst as a cathode offered a high peak energy density of 134.6 mW cm −2, high specific capacity of 856.2 mA h gZn −1 and excellent stability over 180 h at 5 mA cm −2 (10 min per cycle) with a small charge/discharge voltage gap of ∼0.851 V. This work presents a practical strategy for constructing nitrogen-rich catalysts with stable 3D structures.